Measurement of Factors Influencing Village Financial Statements Quality - Cecilia Lelly Kewo; Stella Theodora Kewo (Journal of Economics, Business, and Accountancy Ventura, 2024)
Village finance is in the spotlight of the Republic Indonesia government, where there are many problems with village finance, from budgeting to financial reporting. This cannot be separated from the large disbursement of village funds from the central government to improve village welfare. This study aims to analyze the impact of competency factors, internal controls, and accounting information systems factors on the quality of village financial statements. With a population of 227 villages, this study collected samples from 138 villages through simple random sampling. The data that has been collected is then measured by Structural Equation Modeling – Partial Least Square with an alpha of 5%. The results show that the competencies have a positive significant effect on the quality of village financial statements. Likewise, internal control and accounting systems each positively affect the quality of village financial statements. This research has implications for local governments to increase training for village apparatus, expand internal control socialization and improve infrastructure related to computers and internet networks.